Variables Pedagógicas Que Causan E Influyen El Absentismo Estudiantil En Las Clases De Matemática De La Escuela Superior Pedagógica De Namibe-Angola - Sarmento-dos-Santos, Ana Paula; Chaves-Barboza, Eduardo; Díaz de la Guardia, José Javier Romero (European Scientific Journal, ESJ, 2017)
The article aims to comparatively analyse the pedagogical variables that cause and influence the absenteeism of the students in math classes Pedagogical School of Namibe (Angola); the perception of teachers (population 44, sample 41) and students (population 131, sample 99) are contrasted, all of them of the second and the third level in the Degree of Physics and Chemistry. To achieve this objective a type questionnaire Likert scale are applied, it has four levels of agreement and fourteen pedagogical variables related with absenteeism. Descriptive and inferential statistics are applied on the data, also correlation analysis with Pearson coefficient, variance analysis using Mann-Whitney and Kruskal-Wallis tests, and multivariate analysis Factorial Kaiser-Meyer-Olkin are performed with Varimax rotation. As a result is obtained that the student disinterest and lack of ability of teachers to develop effective and motivating teaching are variables that cause and explain absenteeism in math classes. The analysis results show that some ways to reduce absenteeism are achieve stability of teachers in courses, increase opportunities for teachers to meet their students and achieve an environment of respect, solidarity and support for students.